2007
DOI: 10.3168/jds.2006-549
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Claw Health and Milk Yield in Dairy Cows on Elastic or Concrete Flooring

Abstract: This article reports on the effects of elastic (rubber) flooring compared with concrete flooring on claw health and milk yield in dairy cows. Milk yield and activity data of 53 complete lactations from 49 cows were recorded by an automatic milking system in the University of Munich Livestock Center dairy herd. Cows were kept in a loose housing system on concrete-slatted or rubber-matted slatted flooring. Claws were trimmed and measured linearly in combination with claw lesion diagnosis 3 times during one lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 17 publications
(18 reference statements)
6
43
2
3
Order By: Relevance
“…Haufe et al (2009) reported a slight effect of floor type (solid rubber, mastic asphalt, and slatted concrete floor) on claw health, whereas Vanegas et al (2006) reported that foot lesions did not differ between floor types, although locomotion score was higher for concrete-exposed cows than for those on rubber. In contrast, Kremer et al (2007) and Fjeldaas et al (2011) reported a higher incidence of sole ulcers for rubber-exposed cows compared with those on concrete.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Haufe et al (2009) reported a slight effect of floor type (solid rubber, mastic asphalt, and slatted concrete floor) on claw health, whereas Vanegas et al (2006) reported that foot lesions did not differ between floor types, although locomotion score was higher for concrete-exposed cows than for those on rubber. In contrast, Kremer et al (2007) and Fjeldaas et al (2011) reported a higher incidence of sole ulcers for rubber-exposed cows compared with those on concrete.…”
Section: Introductionmentioning
confidence: 74%
“…Previous studies reported that cows kept on rubber mats generally showed greater activity and they stood in the walking area longer than cows on mastic asphalt or slatted concrete floor (Kremer et al, 2007;Haufe et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Manske (2002) determined a lower incidence of sole ulcers on rubber mats. Kremer et al (2007) established more sole ulcers on elastic slatted flooring compared with concrete solid slatted flooring. Benz (2007) refers to the fact, that infectious claw lesions can be hardly influenced by elastic layers.…”
Section: Discussionmentioning
confidence: 99%
“…A floor surface which is too rough causes rapid wear of animal hooves and grazes on other parts of the body, and floors with an initially ideal surface may become too rough or slippery because of degradation (de Belie 1997). On the other hand, despite the fact that soft flooring provides good locomotion comfort for dairy cows, some incidents and diseases are more common on soft floorings than on concrete (Kremer et al 2007), and a moderate abrasion by the flooring is required to prevent claw overgrowth (Kremer et al 2007, Telezhenko 2007. Thus a single factor or parameter, such as wearing and slipperiness used here as examples connected to cleanness, is complicated in practice.…”
Section: Animal Welfare and Hygienementioning
confidence: 97%